WUJUD MORAL ISLAM DALAM LEMBAH KEHIDUPAN (KUMPULAN CERITA PENDEK) KARYA M. HUSSEYN UMAR DENGAN PENDEKATAN PRAGMATIK - Kingkin Fadhilah Fitrianna; YB Maridja (CARAKA, 2016)
The purpose of this study was to describe (1) the characters, characterizations, and background, (2) a form of Islamic morals in the Lembah Kehidupan (Collection of Short Stories) by M. By Husseyn Umar. The research is a qualitative research. The research data is qualitative data in the form of dialogue phrases, sentences, paragraphs or units in Lembah Kehidupan (Collection of Short Stories) by M. Husseyn Umar. The primary data source is the Lembah Kehidupan (Collection of Short Stories) by M. Husseyn Umar issued by PT. Fikahati Aneska cooperation with BANI Arbitration Centre in 2013. The research instrument is the researchers themselves are equipped with a set of theories about the characters, characterizations, background, theoretical form of Islamic moral and pragmatic theory of literature. Data collection methods using a reading method, record, and library. Analysis data was conducted using the qualitative descriptive technique. The results of the study are as follows. (1) Figures, characterizations, and background in the Lembah Kehidupan (Collection of Short Stories) consists of, the main character is Hamid, he is a hard-working (short story "Antara Manusia dan Hukum"), Sudaraman is discipline (short story "Pelantikan"), Harun is a religious (short story â€œPerkawinanâ€), Kaharudin is a candor (short story "Menjual Bantuan"), Mr. Sharif is a hard-working (short story "Lembah Kehidupanâ€). The background used in the Lembah Kehidupan (Collection of Short Stories) that is setting of the place, time, and social background. (2) a form of Islamic morality contained in the Lembah Kehidupan (Collection of Short Stories) by M. Husseyn Umar includes a) a form of Islamic morality based on human relationship with yourself is hard work, courageous, patient, b) a form of Islamic morality based on human relationships through others that responsibility, honest, firm establishment, shame, trust, love and attention to her husband, between friends, respect, superiors and subordinates, parents advices to children, the love of parents to children, the love child of parents , the love between friends, the responsibility of parents advices to children, the responsibility between friends, c) moral form of Islam based on human relationship with God is grateful, pray to God, pray, and faith.